YIELD ASSESSMENT OF BEETROOT AND POTATO, CULTIVATED ON ORDINARY CHERNOZEM CONTAMINATED WITH HEAVY METALS - N. V. Gromakova (Овощи России)
Potato and table beet are traditional crops in vegetable growing in Russia. It is important to produce high, environmentally friendly crops. The effect of mineral fertilizers to reduce the accumulation of heavy metals (HM) in beetroot and potatoes was studied in the experiment on ordinary chernozem. The soil was supplied with Cu, Zn and Pb, as a mineral fertilizer, Azofosca (N16%, P16%, K16%) was also used in the experiment. Salts of heavy metals and fertilizer were introduced in accordance with the developed scheme of experiment: 1. Control; 2. Cu100Zn100Pb100; 3. N60P60K60 + Cu100Zn100Pb100. In the soil, the total stock of metals and their mobile forms were determined, and the content of metals and yield were defined in plants. The results of the study showed that for gross forms MRL exceeded in all metals studied, and in mobile forms of Cu and Pb. With the joint application of HM to the soil with fertilizer, the mobility of metals decreased. In the root crops, the excess of MRL for Cu, Zn and Pb was observed. With the joint application of HM with fertilizers, the content of Zn and Pb in the root crops decreased below the MRL. Beet was more likely to accumulate HM than potatoes. The yield of beetroot and potato beets varied greatly in terms of experiment options. Thus, the introduction of HM into the soil significantly reduced the yield of beets. The introduction of fertilizers together with HM contributed to an increase in yield, but for beet, the yield level here was also lower than in the control variant. When growing roots in technogenically transformed conditions, the potato is characterized by sufficiently higher yield stability and does not accumulate toxic amounts of HM on a fertilized ground.